EVALUASI IMPLEMENTASI PEMBELAJARAN PRAKTIK SELAMA PANDEMI COVID-19 PROGRAM STUDI PENDIDIKAN TATA RIAS DAN KECANTIKAN - Flowriza, Erin; Rahmiati, Rahmiati (Jurnal Pendidikan Teknologi Kejuruan, 2021)
Quantitative data analysis carried out included data descriptions and respondent's level of achievement in 4 (four) components, namely: context (context), input (input), product (process), output (result). Based on the results of the research that has been done, all incoming data meet the requirements for processing and analysis. Quantitative data were collected through a questionnaire consisting of 27 questions that had been tested for validity and reliability. Furthermore, the questionnaire was given to 104 students of the Faculty of Tourism and Hospitality in the Department of Makeup and Beauty in 2018 which were filled in online via google form to answer the questions given about the evaluation of the implementation of practical learning during the Covid-19 pandemic, the make-up and beauty study program. . statistical data of research evaluation of the implementation of practical learning during the Covid-19 pandemic, Makeup and Beauty Education Study Program. The table above shows that the number of data (N) is 104, mean 106.66, median 107, mode 109, standard deviation 6.99, variance 48.86 range 33, minimum value 91, maximum value 124, and total Overall score of 11093. To complement the research data collected through questionnaires, the researcher also collected data by conducting interviews with several respondents, namely 4 lecturers of makeup and beauty at UNP. When conducting interviews, data were recorded and important points were recorded from the contents of the interview. Interview data were collected by researchers related to components in the evaluation of practical learning during the Covid-19 pandemic of make-up and beauty education study programs, namely components of context (context), input (input), process (process), and product (result).